(untitled) (Indonesian Journal of Agricultural Research, 2023)
This study was aimed to determine the growth and development of Broiler chicken carcass and components at different sex and age . The method used in this study is the Huxley Y = a x b allometric equation which is transformed into a logarithm equation Log Y = Log a + b Log X. This research was conducted in the Cage of the Animal Production Department of the Faculty of Agriculture, Halu Oleo University. The parameters observed in this study were the carcass and carcass parts. Based on the results of the study showed that the growth coefficient of male and female broiler carcasses were not significantly different (P>0.05) which meant that they had a time of early development when compared to the growth of parts of the body as a whole. The growth and development patterns of the carcasses of both male and female broiler chickens at the age of 0 - 5 weeks is relatively the same.